The construction of meaning in the discourse of electronics: A systemic-functional approach. La construcción del significado en el discurso de la electrónica: un discurso sistémico-funcional - González Pueyo, Mª Isabel (Estudios Ingleses de la Universidad Complutense, 2003)
This paper a concerned with the lexico-grammatical resources the English language uses to construct meaning in engineering texts, particularly in chase texts addressed to students where verbal and non-verbal language —i.e. mathematics, cables and graphs— combine. The initial hypothesis is that non-verbal representation text can be analysed in the same way as any verbal text and that both verbal and non-verbal texts integrate in such away that they constitute a powerful social-semiotic resource to create specific ways of meaning. Drawing on genre and on systemic theory, which views language as a meaning making system rather than an expression-making one, several texts from the field of electronics have been analysed in the light of the three linguistic metafunctions proposed by Halliday (1978, 1 985a), namely, ideational, interpersonal and textual.